Mechanistic Aspects of Aqueous Heterogeneous Radical Polymerization of Styrene under Compressed CO2. Issue 14 (8th May 2017) - Hadzir, Noor Hadzuin Nik; Dong, Siming; Kuchel, Rhiannon P.; Lucien, Frank P.; Zetterlund, Per B.
Abstract : Radical polymerization of styrene in aqueous emulsions pressurized by CO2 is investigated with a view to development of low energy miniemulsion polymerization. These polymerizations do not proceed as true miniemulsion polymerization systems, but are also characterized by a significant contribution of particle formation via secondary nucleation as in an ab initio emulsion polymerization. Abstract : Radical polymerization of styrene in aqueous emulsions pressurized by CO2 has been investigated with a view to development of low energy miniemulsion polymerization. The general requirement of high energy mixing to generate miniemulsions comprising sub‐micrometer‐size monomer droplets has long been an impediment to wide‐spread industrial application. It is demonstrated by use of online dynamic light scattering and visual observation that CO2 pressurization to the so‐called transparency pressure of an emulsion comprising styrene/hexadecane/Dowfax 8390 (anionic surfactant)/water leads to a decrease in droplet size as well as an increase in emulsion stability. However, mechanistic investigations of radical polymerization under CO2 pressure reveal that these polymerizations do not proceed as true miniemulsion polymerization systems (i.e., via exclusive monomer droplet nucleation), but are also characterized by a significant contribution of particle formation via secondary nucleation as in an ab initio emulsion polymerization.